Beautiful mystery A Chief Inspector Gamache Novel - Penny, Louise (New York : Minotaur Books, 2012)
No outsiders are ever admitted to the monastery of Saint-Gilbert-Entre-les-Loups, hidden deep in the wilderness of Quebec, where two dozen cloistered monks live in peace and prayer. They grow vegetables, they tend chickens, they make chocolate. And they sing. Ironically, for a community that has taken a vow of silence, the monks have become world famous for their glorious voices, raised in ancient chants whose effect on both singer and listener is so profound it is known as "the beautiful mystery." But when the renowned choir director is murdered, the lock on the monastery's massive wooden door is drawn back to admit Chief Inspector Armand Gamache and Jean-Guy Beauvoir of the Surete du Quebec. There they discover disquiet beneath the silence, discord in the apparent harmony. One of the brothers, in this life of prayer and contemplation, has been contemplating murder. As the peace of the monastery crumbles, Gamache is forced to confront some of his own demons, as well as those roaming the remote corridors. Before finding the killer, before restoring peace, the Chief must first consider the divine, the human, and the cracks in between.
Keywords: Gamache, Armand (Fictitious character); Murder -- Investigation; Monastaries; Monks; Fiction -- Murder & Investigation -- General; Quebec; Fiction; Mystery fiction